Health-Related Quality of Life Outcomes in PARADIGM-HF. (August 2017) - Lewis, Eldrin F.; Claggett, Brian L.; McMurray, John J. V.; Packer, Milton; Lefkowitz, Martin P.; Rouleau, Jean L.; Liu, Jiankang; Shi, Victor C.; Zile, Michael R.; Desai, Akshay S.; Solomon, Scott D.; Swedberg, Karl
Abstract : Background: Patients with heart failure and reduced ejection fraction have impaired health-related quality of life (HRQL) with variable responses to therapies that target mortality and heart failure hospitalizations. In PARADIGM-HF trial (Prospective Comparison of ARNI [Angiotensin Receptor–Neprilysin Inhibitor] With ACEI [Angiotensin-Converting–Enzyme Inhibitor] to Determine Impact on Global Mortality and Morbidity in Heart Failure), sacubitril/valsartan reduced morbidity and mortality compared with enalapril. Another major treatment goal is to improve HRQL. Given improvements in mortality with sacubitril/valsartan, this analysis provides comprehensive assessment of impact of therapy on HRQL in survivors only. Methods and Results: Patients (after run-in phase) completed disease-specific HRQL using Kansas City Cardiomyopathy Questionnaire (KCCQ) at randomization, 4 month, 8 month, and annual visits. Changes in KCCQ scores were calculated using repeated measures analysis of covariance model that adjusted for treatment and baseline values (principal efficacy prespecified at 8 months). Among the 8399 patients enrolled in PARADIGM-HF, 7623 (91%) completed KCCQ scores at randomization with complete data at 8 months for 6881 patients (90% of baseline). At 8 months, sacubitril/valsartan group noted improvements in both KCCQ clinical summary score (+0.64 versus −0.29; P =0.008) and KCCQ overall summary score (+1.13 versus −0.14; P <0.001) in comparison to enalapril group and significantly less proportion of patients with deterioration (≥5 points decrease) of both KCCQ scores (27% versus 31%; P =0.01). Adjusted change scores demonstrated consistent improvements in sacubitril/valsartan compared with enalapril through 36 months. Conclusions: Change scores in KCCQ clinical summary scores and KCCQ overall summary scores were better in patients treated with sacubitril/valsartan compared with those treated with enalapril, with consistency in most domains, and persist during follow-up beyond 8 months. These findings demonstrate that sacubitril/valsartan leads to better HRQL in surviving patients with heart failure. Clinical Trial Registration: URL:http://www.c linicaltrials.gov . Unique identifier: NCT01035255. Abstract : Supplemental Digital Content is available in the text.